BLV: Lessons on vaccine development - Abdala, Alejandro Ariel (2019)
Vaccination against retroviruses is a challenge because of their ability to stably integrate into the host genome, undergo long-term latency in a proportion of infected cells and thereby escape immune response. Since clearance of the virus is almost impossible once infection is established, the primary goal is to achieve sterilizing immunity. Besides efficacy, safety is the major issue since vaccination has been associated with increased infection or reversion to pathogenicity. In this review, we discuss the different issues that we faced during the development of an efficient vaccine against bovine leukemia virus (BLV). We summarize the historical failures of inactivated vaccines, the efficacy and safety of a live-attenuated vaccine and the economical constraints of further industrial development.